Ethnobotanical documentation of medicinal plants and traditional fermented foods of the Mishing community in Jorhat district of Assam, India - Gogoi, Preronaa; Konwar, Surajeet; Das, Sujata; Das, Dashami; Doimari, Rituporna; Sonar, Tinnu; Doley, Sita (Ethnobotany Research and Applications, 2026)
Background: The current study documents the traditional knowledge of ethnomedicinal plants, and ethnic fermented foods and beverages used by the Mishing community in the Jorhat district of Assam, aiming to understand their contribution to primary healthcare and cultural practices. Methods: Ethnobotanical surveys were carried out in 10 villages of Jorhat district between March 2024 and 2025 through semi-structured questionnaires, individual interviews, and focused group discussions with 50 key informants, and the plants were collected, taxonomically identified using standard floras and online databases, and then analyzed quantitatively using indices such as Use Value (UV), Informant Consensus Factor (ICF), Relative Frequency Citation (RFC) and Fidelity Level (FL%). Results: A total of 94 medicinal plant species belonging to 56 families were recorded, with Lamiaceae and Rutaceae being the most represented families, and leaves constituting the most frequently used plant part for treating ailments including diabetes, dysentery, jaundice, gastric disorders, infections, kidney stones, and allergies. Ocimum sanctum and Paederia foetida had the highest use value (UV) of 1. The highly cited or high RFC value containing plant species included O. sanctum and Azadirachta indica (0.96). Acorus calamus, Aegle marmelos, O. sanctum and P. foetida had the highest FL%. In addition, two ethnic fermented foods (Numsing and Iku) and two traditional rice-based fermented beverages (Po: ro apong and Noggin apong) were documented, prepared using diverse medicinal plant additives and household techniques that enhance preservation, palatability, and nutritional value. Conclusions: The results reveal a rich repository of ethnomedicinal knowledge and fermentation practices that support community-based primary healthcare and nutrition among the Mishing people. Immediate scientific validation and conservation-oriented documentation are required to safeguard this rapidly declining indigenous knowledge system. Keywords: Ethnomedicine; Mishing; Traditional knowledge; Ailment; Use Value; Informant Consensus Factor (ICF); Relative Frequency Citation (RFC) ; Fidelity Level (FL%); Treatment, Fermented food.